Airport responsibility for wildlife management - Rillstone, Douglas J. (Transportation Research Board, 2013)
"compiles the laws and regulations pertaining to wildlife hazard management and discusses mitigation techniques applicable to airport operators."
Caption title.
"July 2013."
At head of title: Airport Cooperative Research Program.
"Sponsored by the Federal Aviation Administration."
"Prepared under ACRP Project 11-01, 'Legal Aspects of Airport Programs'."
Keywords: Airports -- Bird control -- United States.; Wildlife management -- United States.; Airports -- United States -- Safety measures.; Airports -- Law and legislation -- United States.; Aircraft accidents -- United States -- Prevention.; United States.; elektronické knihy; electronic books